Indoor Localization with smartphone using BLE iBeacon - Dương, Ngọc Sơn (2021)
In this thesis, an indoor positioning system based on iBeacon and phone sensors was presented. In this thesis, we propose a real-time indoor positioning system in smartphone via BLE iBeacon signal. In which, we used embedded sensors for displacement calculation and BLE iBeacon signal as a calibrated opportunity for sensor-based IPS. Firstly, we investigate the problems associated with the uncertainty of RSS, then offer solution for RSS-based locating moving target under low sampling rate. Secondly, we proposed method of improving accuracy for LSE method. Improved LSE-based position then fused with PDR-based position using Kalman filter to produce more accurate positions. The accuracy of the proposed approaches proved high persuasion for service providers to deploy this low-complexity system for various location-based services.